"A Man With a Loving Heart": A Systematic Review of Male Involvement in Cervical Cancer Screening in Africa - Teluleko N. Maseko; Joyce M. Tsoka-Gwegweni; Xolisile Dlamini (Frontiers Media S.A., 2024)
ObjectiveThis review assessed men's involvement and the predictors of their involvement in cervical cancer screening.MethodsWe conducted a comprehensive search of the following electronic databases: PubMed, EMBASE, CINAHL, African, Web of Science, and Scopus. The search was limited to articles published between January 2010 and January 2023.ResultsA total of 17 studies met the inclusion criteria and were included for this review. More than 50% of the studies emphasised the relevance of male involvement in cervical cancer prevention in Africa and demonstrated the critical importance of this as a strategy.ConclusionThe results revealed that a significant proportion of male participants had a restricted comprehension of cervical cancer. Nevertheless, they expressed their willingness to provide backing for cervical cancer screening contingent upon their informed consent.